The Moderating Role of Risk Monitoring Committee on the Effect of Risk Disclosure on Financial Performance in Islamic Banks - Laely Aghe Africa; Dian Agustia (Australasian Accounting, Business and Finance Journal, 2023)
This study examines the impact of risk disclosure on the financial performance of Indonesian Islamic banks and the ability of the Risk Monitoring Committee to moderate them. Quantitative research. OJK regulations in 2014 limited the selection of samples of Islamic banks so that the sample used is 72 Islamic banks in Indonesia from 2014 to 2021. These measures were calculated using the Statistical Package for the Social Sciences (SPSS 20) software SPSS tool (Statistical Package for the Social Sciences). The variables used are the dependent variable (ROE), independent variable (RD), moderating variable (RMC), and control variables (FDR, NPF, and CAR ratios). The findings show that the lower the risk disclosure, the lower the risks the bank faces and the higher it is financial performance. The existence of a risk monitoring committee can moderate the impact of risk disclosure on financial performance. Future research is expected to be able to compare Islamic and conventional commercial banks by adding variations and increasing the number of samples. Additional research can determine whether the findings of this study apply to Islamic banks in other countries. This research is beneficial for banking decision-makers because the completeness and risk assessment are always under the supervision of the risk disclosure committee. This study also adds novelty to the measurement of risk disclosure by utilizing the average inherent risk value.
Keywords: Risk Disclosure; Risk Monitoring Committee; Financial Performance; Islamic Bank